Morphological Interference in the Form of Malay Language Affixation Panai Dialect in the Use of Writing Language (Narrative Text) in 5th Grade of Primary School No. 112202 in Middle Panai District. - Giatno Giatno; Hadi Wisman; M. Oky Ferdian Gafari (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aim of this research to find Morphological Interference in the Form of Malay Language Affixation Panai Dialect. The data is taken in writing language or Narrative text in 5th grade students of Primary School no. 112202 in Middle Panai Disctrict. The methodology research uses qualitative research and descriptive research. The result is confixes more dominant to be found in Narrative text based on Malay language in Panai dialect.